Lietuviškas Adomo Mickevičiaus autografas - Zinkevičius, Zigmas (Baltistica, 1983)
Adam Mickiewicz’s Lithuanian autographThe article examines the only known text in Lithuanian written by A. Mickiewicz (the text is kept in A. Mickiewicz's museum in Paris). It consists of fragments of three Lithuanian folk songs sung to A. Mickiewicz by L. Korylski (Kobecki). On the basis of the photocopy of the text and the analysis of extralinguistic data as well as experimental data, the author of the article comes to the following conclusions:The fragments of the Lithuanian folk songs were sung by L. Korylski in his native Northern Samogitian dialect spoken in the area between Palanga, Darbėnai and Lenkimai. This dialect greatly differs from Standard Lithuanian, and A. Mickiewicz cannot have been acquainted with it. Yet, he was familiar with the Aukštaičiai variants (dialects akin to Standard Lithuanian) of the first two fragments. Therefore, in recording them, A. Mickiewicz vacillated between Korylski's Samogitian and his own Aukštaičiai forms, which was the cause of their quarrel mentioned by A. Mickiewicz's children (this disproves the conclusion reached by M. Brensztejn and Otrębski that the children may have failed to remember it exactly). The third fragment was not familiar to A. Mickiewicz. He recorded it by ear, not fully understanding the Samogitian text, at least at the beginning.The analysis of the said text and extralinguistic data shows that Lithuanian cannot have been absolutely unknown to A. Mickiewicz. Yet, we have no data which would enable us to establish the degree of his knowledge of Lithuanian.
Keywords: Adam Mickiewicz; autograph; lithuanian text